2021
DOI: 10.3390/toxins13040243
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of Multiple Mycotoxins in Urine by GC–MS/MS: A Pilot Study on Patients with Esophageal Cancer in Golestan Province, Northeastern Iran

Abstract: A pilot study to investigate the occurrence of 10 mycotoxins (deoxynivalenol, DON; 3-acetyldeoxynivalenol, 3-ADON; 15-acetyldeoxynivalenol, 15-ADON; fusarenon-X, FUS-X; diacetoxyscirpenol, DAS; nivalenol, NIV; neosolaniol, NEO; zearalenone, ZON; zearalanone, ZAN; T-2 toxin, T-2; and HT-2 toxin, HT-2) in esophageal cancer patients was performed with the urinary biomarkers approach in Golestan, Iran. Urine multimycotoxin analysis was performed by dispersive liquid–liquid microextraction and gas chromatography–ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Contrary to these results, Warth et al [ 25 ] did not determine free DON in analyzed urinary samples. Niknejad et al [ 26 ] studied the multi-mycotoxin urinary levels in healthy volunteers and esophageal cancer patients, and reported DON presence in only one sample from healthy volunteers at a concentration of 8.42 µg/L.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to these results, Warth et al [ 25 ] did not determine free DON in analyzed urinary samples. Niknejad et al [ 26 ] studied the multi-mycotoxin urinary levels in healthy volunteers and esophageal cancer patients, and reported DON presence in only one sample from healthy volunteers at a concentration of 8.42 µg/L.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found the co-occurrence of the mycotoxins (NEO, HT-2, and T-2) in the urine samples. While T-2 toxin was only present in the oesophageal cancer group, HT-2 was the most common mycotoxin in combination present in all the co-occurring samples, followed by NEO, which was present in two of the three multi-contaminated urine samples [48]. Although the relationship between mycotoxin exposure and oesophageal cancer incidence was not established, and since cancer is a multifactorial disease, other cofounding factors could play a role in the development of the disease.…”
Section: Mycotoxin-linked Mutations and Increased Esophageal Cancer R...mentioning
confidence: 94%
“…The sixteen included studies comprised of fifteen case-control studies [35][36][37][38][39][40][41][42][43][44][45][46][47][48] and one cohort study [49]. Twelve (75%) of the studies were from Asia [35][36][37][38]40,[42][43][44][45]48,49], while the remaining four (25%) of the studies were conducted in Africa. The studies from Africa were carried out in South African [41], Sudanese [39], and, in two studies, from Tunisian populations [46,47].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine samples constitute a complex matrix, in which mycotoxins presented in trace amounts may be masked by some interfering compounds, making a clean-up step necessary. Different techniques such as liquid-liquid extraction (LLE), solid phase extraction (SPE), dispersive liquid-liquid micro extraction (DLLME), QuEChERS, and immunoaffinity columns (IAC) have been reported in the literature for mycotoxin determination in urine [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%